Risk of postoperative bleeding and thromboembolic events in anticoagulated patients undergoing transurethral resection of bladder tumors - Thomas Paul Scherer; Cici Dam; Uwe Bieri; Daniel Eberli; Raeto Strebel (Therapeutic Advances in Urology)
Background: Transurethral resection of the bladder (TURB) harbors a high-risk for postoperative bleeding, especially in patients requiring anticoagulation. Recently, direct oral anticoagulants (DOACs) have become a popular alternative to vitamin K antagonists (VKAs), though their impact on TURB complications remains unclear. Objectives: To assess the postoperative complications of TURB from patients taking DOACs and VKAs. Design: Retrospective cohort study. Materials and methods: We retrospectively identified anticoagulated patients undergoing a TURB at our institution between 2012 and 2022 and divided them into two groups: whether they received VKA or DOAC. Follow-up of each patient was performed for 3 months. Occurrence and time to event of postoperative bleeding and thromboembolic events were recorded. A multivariable regression analysis was performed to assess risk differences. Results: A total of 167 patients (11.7%) fulfilled the inclusion criteria, of which 102 patients (61.1%) received a DOAC and 65 patients (38.9%) a VKA. Postoperative bleeding led to re-catheterization in 13 (12.8%) DOAC and 6 (9.2%) VKA patients ( p  = 0.49) and re-intervention in 7 (6.9%) DOAC and 4 (6.2%) VKA patients ( p  = 0.86). Blood transfusions were administered to 3 DOAC patients (2.9%), none in the VKA group. No thromboembolic events were reported. Conclusion: TURB carries low morbidity in anticoagulated patients. Thromboembolic events and the need for blood transfusion are infrequent. No substantial difference between the postoperative bleeding risk of patients receiving DOAC or VKA was found. All bleeding complications occurred within 2 weeks, marking it a potentially safe point in time to restart the OAC thereafter.